Digital health: current applications, challenges, and future directions for enhancing healthcare quality and safety - Hu, Saidi; Song, Danyang; Wan, Siran; Zhang, Shunhong; Luo, Chenchen; Li, Nian; Liu, Guangyue; Graça Espírito Santo Vasconcelos, Jailson da; de Carvalho, Leonilde Lavres Ceita; Neobísi, Eveline; da Costa, Monazeri Lima Bragança; Etchu Takounjou, José; et al. (Frontiers in Public Health, 2025)
Digital Health Technologies (DHTs) have become a cornerstone of modern healthcare, significantly improving quality and safety across clinical practice, public health, and medical research. Originating in the mid-to-late 20th century, DHTs have facilitated substantial progress in personalized medicine, predictive analytics, and remote patient monitoring through the implementation of artificial intelligence (AI), wearable devices, and telemedicine platforms. During the Coronavirus Disease 2019 (COVID-19) pandemic, these technologies proved indispensable for epidemic surveillance and precision containment, while also mitigating healthcare access disruptions. Nevertheless, critical challenges including the digital ethics and equity, technical and regulatory policy restrictions, privacy and data security concerns, and clinical workflow integration issues remain to be addressed. This narrative review explores the transformative role of DHTs throughout the disease management continuum—from prevention to prognosis—and evaluates their contributions to healthcare quality and safety. It also provides strategies for stakeholders to address existing barriers. By overcoming these challenges, DHTs can further elevate healthcare standards, fostering a safer and more efficient global healthcare system.